Adsorbed protein on P25 nanoparticlessynthesis, characterization and electrochemical property - Weerachon Phoohinkong; Thitinart Sukonket; Kanokthip Boonyarattanakalin (My University, 2018)
Keratin modification on surface of titanium dioxide P25 was carried out from titanium dioxide suspension and keratin solution extracted from swine wool. The existence of amide component, protein functional groups dissociated to active protein moieties and attached to titanium dioxide surface in form of hybrid nanomaterial were characterized by Fourier-transform infrared spectroscopy (FT-IR). The keratin protein decorated on particle surfaces was observed by Field Emission Scanning Electron Microscopy (FESEM). Chemical states and bonding at the nano-biomolecule interfaces with titanium dioxide were investigated using X-ray Photoelectron Spectroscopy (XPS). Protein concentration is considered as roles for protein modification, surface bonding, chemical states and protein adsorption. The Ti3+ and Ti2+ surface and high adsorption degree can be obtained at low concentration of protein solution with P25. However, the strong bonding between protein and TiO2 obtained in high protein concentration with Ti3+ and Ti2+ species result disappear for Ti3+ and Ti2+ XPS peaks. The adsorbed protein reveals secondary structure of random coil keratin with strong bonding conjugated to the titanium dioxide surface. The strong binding between protein and TiO2 surface in this novel protein-TiO2 hybrid material shows a promising alternative way for advance tunable electronic structure and charge transport mechanism which enhance electrochemical capacitance by mean of double layer and pseudo-capacitive behavior.
Keywords: Protein Adsorption; Titanium Dioxide; Surface Modification; Dyeing and Modifying Textile Fibers